Avaliação da pegada de escassez hídrica: um comparativo entre duas metodologias de pegada hídrica aplicada no campus Sorocaba da Universidade Federal de São Carlos - Marins, Manoela Anechini Simões (2020)
The water crisis has been highlighted on the international scene. Although the water available on the planet is sufficient to meet the demands, its poor distribution compromises the supply in various regions of the world and at specific times of the year. Several communities have been developing tools to estimate the potential impacts of water use by man, and a tool that is gaining prominence is the water footprint. Proposed by two communities, the Water Footprint Network (WFN) and the Life Cycle Assessment (LCA) standardized by ISO 14046: 2017, the tool measures the appropriation of water resources by man and their impacts. Thus, this research aims to compare the two water footprint approaches and the application of the two methodologies in a Federal Institution of Higher Education (IFES) located in the Sorocaba River Basin, as a support for decision making. Although the two methodologies present consistent subsidies, the WFN focuses on the volume of water consumed, it is more efficient in raising awareness about the amount of water appropriate for man and less complex for application, however there are uncertainties regarding the calculation of the gray water footprint, because it does not assess the potential impact of the pollutant, but the amount of water needed for its dilution in the basin. ISO 14046: 2017 is more efficient in demonstrating the potential impacts and risks related to the use of water resources, but it is complex and requires greater efforts for application. The norm does not define the method leaving the subjective choice. In addition, the methodology does not include the use of green water. For the application on campus, the available data was sufficient to carry out the assessment of water scarcity from direct water use. In the application of the methodologies, the unsustainability of the basin was identified between the months of May and November in both methods, however, the LCA approach showed greater sensitivity in the result, presenting water scarcity in the annual basis, which did not occur in the WFN.